Media activism in the digital age - Pickard, Victor W.; Yang, Guobin (London; New York : Routledge, 2017)
The growing subfield of media activism studies has gained wide attention in recent years, but little consensus exists regarding its central questions and concerns. This book begins to chart an evolving research agenda by providing a cross-section of provocative work in this area. Victor Pickard and Guobin Yang have assembled essays by leading scholars and activists to provide case studies of feminist, technological, and political interventions during different historical periods and at local, national, and global levels. Looking at the underlying theories, histories, politics, ideologies, tactics, strategies and aesthetics, the book takes an expansive view of media activism. It explores how varieties of activism are mediated through communication technologies, how activists deploy strategies for changing the structures of media systems, and how governments and corporations seek to police media activism. From memes to zines, hacktivism to artivism, this volume considers activist practices involving both older kinds of media and newer digital, social, and network-based forms. The book captures an exciting moment in the evolution of media activism studies and offers an invaluable guide to a vibrant and evolving field of research.
What is media activism / W. Lance Bennett -- Introduction / Victor Pickard and Guobin Yang -- Communication for Social Change / Sandra Ristovska -- The Future of Digital Enfranchisement / Jeff Landale and Sascha Meinrath -- Towards Transformative Media Organizing: LGBTQ and Two-Spirit media work in the United States / Sasha Costanza-Chock, Chris Schweidler, Teresa Basilio, Meghan McDermott, and Puck Lo -- Studying Media at the Margins: Learning from the Field / Clemencia Rodriguez -- The Online Translation Activism of Bridge Bloggers, Feminists, and Cyber Nationalists in China / Guobin Yang -- Policy Interventions / Tim Libert -- The Battle over Diversity at the FCC / Mark Lloyd -- Feminist Activism and U.S. Communications Policy / Carolyn M. Byerly -- A return to prime time activism: social movement theory and the media / Des Freedman -- New Political Genres / Jonathan pace -- Cahiers de doleance 2.0: crowd-sourced social justice blogs and the emergence of a rhetoric of collection in social media activism / Paolo Gerbaudo -- Data activism as the new frontier of media activism / Stefania Milan -- The Use of the Geoweb for Social Justice Activism / Leslie Regan Shade, Evan Hamilton, and Harrison Smith -- Feminism's Digital Wave / Rosemary Clark -- Feminists, Geeks, and Geek Feminists: Understanding Gender and Power in Technological Activism / Christina Dunbar-Hester -- Analog Girl in a Digital World: Hip Hop Feminism and Media Activism / Aisha Durham.
Includes bibliographical references and index.
Keywords: Mass media -- Social aspects; Mass media -- Political aspects; Social media -- Political aspects; Digital media -- Political aspects